關於放棄臨床無效治療的倫理學思考: Renouncing Futile Treatment: Ethics Considerations - GUO, Yongsong (International Journal of Chinese & Comparative Philosophy of Medicine, 2000)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 對於沒有臨床救治希望的病人，要不要繼續治療？誰有最終的決定權？這既是臨床醫療問題，又是一個涉及社會倫理法規的問題。對於這樣的病人，不放棄治療可能意味著要消耗更多的醫療資源但又無法挽救病人，但是如果放棄治療，可能會遇到更多的來自社會傳統的、倫理法規的問題。筆者認為，在社會多元化發展的今天，面對臨床無效治療，應在尊重病人或病人家屬有最終決定權的前提下，以一定道德、法規為依據，按照一定的醫療程式和法律手續進行處理，可能是更為符合人道和社會公眾利益的理性選擇。 There has not been a clear medical definition of futility. The concept of futile treatment involves not only medical, but also social, ethical, and legal components. This paper argues that in today’s pluralistic moral circumstances, the patient and/or the family should have the final right to decision regarding futile treatment. Some are opposed to renouncing futile treatment, whatever futility is defined. For them, first, abandoning treatment is in conflict with the physician’s basic duty of offering treatment. Second, giving up treatment also gives up the chance of making medical progress by attempting to treat the patient. Third, the patient would thereby lose the opportunity of prolonging the life. And finally, it would change the good image of the physician (as taking care of the patient). On the other hand, those who support renouncing futile treatment offer different reasons. First, giving up futile treatment will turn out to be respecting the value of the patient’s life. Second, It would help people recognize the natural limit of contemporary medical development. Third, it would facilitate a reasonable pattern of distributing scarce medical resources. And finally, it could reduce the suffering of the patient. As a result, we face a social situation of moral pluralism: people disagree with each other regarding renouncing futile treatment. A difficult practical issue is who has the right to decide renouncing futile treatment. This paper argues that, giving individuals hold conflicting views of life, valoue and morality, the patient should have the final decision power regarding his/her own treatment. If the patient is incompetent, then the family should have the deciding right. In this respect we should overcome the longstanding medical paternalism. In addition, society should establish a prcocedure to regulate and facilitate the decision-mading of renouncing futile treatment. DOWNLOAD HISTORY | This article has been downloaded 16 times in Digital Commons before migrating into this platform.